Convergent-Divergent Validity and Correlates of the Day-to-Day Impact of Vaginal Aging Domain Scales in the MsFLASH Vaginal Health Trial. Issue 1 (4th December 2019) - Hunter, Mary M.; Guthrie, Katherine A.; Larson, Joseph C.; Reed, Susan D.; Mitchell, Caroline M.; Diem, Susan J.; LaCroix, Andrea Z.; Huang, Alison J.
Abstract: Introduction: Clinical research and management of postmenopausal vaginal symptoms have been limited by the lack of validated measures for assessing symptom impact. Aim: To evaluate convergent-divergent validity of the Day-to-Day Impact of Vaginal Aging (DIVA) questionnaire among postmenopausal women with moderate-to-severe vulvovaginal symptoms and identify demographic and clinical factors associated with greater symptom impact. Methods: We examined baseline data from postmenopausal women with moderate-to-severe vulvovaginal itching, pain, irritation, dryness, or pain with intercourse in a randomized trial of vaginal estradiol, moisturizer, or placebo. In addition to completing the DIVA questionnaire, participants rated the severity of their most bothersome vulvovaginal symptom, underwent assessment of vaginal pH and epithelial cytology, and completed other self-report measures including the Female Sexual Function Index (FSFI), Female Sexual Distress Scale (FSDS), and Patient Health Questionnaire-8 for depression (PHQ-8). Main Outcome Measure: The main outcome measures were the unadjusted correlations and multivariable-adjusted associations with 4 DIVA domain scales designed to assess symptom impact on day-to-day activities, sexual functioning, emotional well-being, and body image/self-concept on a scale of 0 to 4. Results: Among 301 women, we detected moderately strong correlations between the DIVA emotional well-being scale and PHQ-8 scores (Pearson correlation coefficient [ r ] = 0.39) and strong correlations between the DIVA sexual functioning scale and FSFI and FSDS scores ( r > 0.50). No significant correlations were detected between any DIVA scales and vaginal pH or epithelial cytology. In adjusted linear-regression analyses, greater vulvovaginal symptom severity was associated with worse DIVA scores for emotional well-being, sexual functioning, and self-concept/body image (average 0.3- to 0.5-point higher DIVA score for each 1-point difference in vulvovaginal symptom severity). Depression symptoms were associated with worse DIVA scores for activities of daily living and emotional well-being (0.2- to 0.4-point higher DIVA score for each 5- point worsening of PHQ-8 score). Women reporting recent sexual activity had lower symptom impact on sexual functioning and self-concept/body image domains (−0.3- to −0.4-point lower DIVA score with weekly sexual activity). Clinical Implications: Findings suggest that the impact of postmenopausal vaginal symptoms on functioning and well-being is greater in women with co-morbid depression symptoms and less frequent sexual activity, independent of symptom severity. Strengths & Limitations: Strengths include the multicenter sample and wide array of measures. Results may not generalize to women with mild symptoms. Conclusion: Our results support the construct validity of the DIVA questionnaire for clinical practice and research and indicate that depression and lower frequency of sexual activity are markers of greater impact of postmenopausal vaginal symptoms on multiple dimensions of functioning and quality of life.